Electron precipitation from EMIC waves: A case study from 31 May 2013. Issue 5 (20th May 2015) - Clilverd, Mark A.; Duthie, Roger; Hardman, Rachael; Hendry, Aaron T.; Rodger, Craig J.; Raita, Tero; Engebretson, Mark; Lessard, Marc R.; Danskin, Donald; Milling, David K.
Abstract On 31 May 2013 several rising tone electromagnetic ion cyclotron (EMIC) waves with intervals of pulsations of diminishing periods were observed in the magnetic local time afternoon and evening sectors during the onset of a moderate/large geomagnetic storm. The waves were sequentially observed in Finland, Antarctica, and western Canada. Coincident electron precipitation by a network of ground‐based Antarctic Arctic Radiation‐belt Dynamic Deposition VLF Atmospheric Research Konsortia and riometer instruments, as well as the Polar‐orbiting Operational Environmental Satellite (POES) electron telescopes, was also observed. At the same time, POES detected 30–80 keV proton precipitation drifting westward at locations that were consistent with the ground‐based observations, indicating substorm injection. Through detailed modeling of the combination of ground and satellite observations, the characteristics of the EMIC‐induced electron precipitation were identified as latitudinal width of 2–3° or ΔL = 1 Re, longitudinal width ~50° or 3 h magnetic local time, lower cutoff energy 280 keV, typical flux 1 × 104 el cm−2 sr−1 s−1 > 300 keV. The lower cutoff energy of the most clearly defined EMIC rising tone in this study confirms the identification of a class of EMIC‐induced precipitation events with unexpectedly low‐energy cutoffs of <400 keV.